Marshaling Resources: - Barbara Yalof (Grounded Theory Review: An International Journal, 2014)
Classic grounded theory (CGT) was used to identify a main concern of online students in higher education. One of the main impediments to studying online is a sense of isolation and lack of access to support systems as students navigate through complex requirements of their online programs. Hypothetical probability statements illustrate the imbalance between heightened needs of virtual learners and perceived inadequate support provided by educational institutions. The core variable, marshaling resources, explains how peer supports sustain motivation toward successful program completion. Understanding the critical contribution virtual interpersonal networks make towards maximizing resources by group problem solving is a significant aspect of this theory.